2005
DOI: 10.1002/jbm.a.30501
|View full text |Cite
|
Sign up to set email alerts
|

Self‐organized nanotubular oxide layers on Ti‐6Al‐7Nb and Ti‐6Al‐4V formed by anodization in NH4F solutions

Abstract: The present work reports the fabrication of self-organized porous oxide-nanotube layers on the biomedical titanium alloys Ti-6Al-7Nb and Ti-6Al-4V by a simple electrochemical treatment. These two-phase alloys were anodized in 1M (NH(4))(2)SO(4) electrolytes containing 0.5 wt % of NH(4)F. The results show that under specific anodization conditions self-organized porous oxide structures can be grown on the alloy surface. SEM images revealed that the porous layers consist of arrays of single nanotubes with a diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
173
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(186 citation statements)
references
References 25 publications
7
173
1
5
Order By: Relevance
“…They were mechanically polished on cloth to 1 μm and ultrasonically cleaned using deionized water and acetone. The samples having area of 1.13 cm 2 were anodized in electrolyte containing 1 M (NH 4 ) 2 SO 4 (POCH) and 0.5 wt% NH 4 F (POCH) [18]. During all anodization processes, the electrolyte was stirred using magnetic stirrer.…”
Section: Methodsmentioning
confidence: 99%
“…They were mechanically polished on cloth to 1 μm and ultrasonically cleaned using deionized water and acetone. The samples having area of 1.13 cm 2 were anodized in electrolyte containing 1 M (NH 4 ) 2 SO 4 (POCH) and 0.5 wt% NH 4 F (POCH) [18]. During all anodization processes, the electrolyte was stirred using magnetic stirrer.…”
Section: Methodsmentioning
confidence: 99%
“…TNTs have been used for different applications such as DNA biosensor [10], detection of bacteria [11] and toxic compounds [12]. TNTs have also been explored for immobilizing proteins and enzymes in biomaterial and biosensor applications [13,14]. Many of the application are related to the photocatalytic activity of TNTs, which is usually evaluated by variations in photocurrent and absorbance under illumination.…”
mentioning
confidence: 99%
“…3 Furthermore, during the last years, it was shown that also other valve metals, such as Zr [15][16][17] and Nb [18,19], and several Ti binary [20][21][22], ternary [23,24] and quaternary alloys [25,26] can be anodized to nanotubular or nanoporous structures in fluoride containing electrolytes. The nanotubes grown on these alloys are similar to pure TiO 2 nanotubes.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%